Biology of Myliobatis goodei (Springer, 1939) a widely distributed eagle ray caught in northern Patagonia - Lopez Cazorla, Andrea Cecilia (2015)
Chondrichthyans play an important role in structuring marine communities. Myliobatis goodie is an eagle ray reported from South Carolina in USA (35°N) to Santa Cuz, Argentina (44°S), however little is known about this species, which is considered Data Deficient by the IUCN. In order to create adequate management strategies for this species, biological information is sorely needed. The objective of this study was to describe the biology of the population of M. goodei and its relationships with season, sex and the geographic features of Anegada Bay, Argentina (from 39.96°S to 40.60°S and from 62.10°W to 62.46°W) during 2008. Specifically, the population structure of M. goodie was studied by sex, seasons and sites, its food habits by seasons and sites, and the reproductive biology by seasons and sex. The results show that M. goodei exhibits seasonal migrations. Young-of-the-year remain in the bay all year long, while adults enter during spring and summer. Juveniles in spring are likely to become first-time mating individuals that migrate into open sea at the end of summer. These individuals would return to give birth for the first time and mate for the second time during the next year at summer. Anegada Bay would then be a mating and nursery area for the species. M. goodei behave as a generalist feeder with a uniform diet composed mainly of bivalves. Seasonal differences in the diet found arise from differences in prey diversity between summer and spring. Spatial differences, however, arise from the different abundances of caprelids and bivalves. Trophic level was 3.2 and it constitutes the first reference for this species, characterizing it as a secondary consumer.